TOPOLOGICAL SURFACE MAPPING USING ULTRASONIC WAVE - Nur Farizky, Muhammad
In the surface topology mapping process, ultrasonic sensors are often designed with the position of the transmitter and the receiver at the same place, so that the receiver receives ultrasonic wave which come from the reflection by an object which lies at the front of the sensor. Since the echo might come from the reflection by another object, the result of the mapping process can be less accurate. In this research, a surface topology mapping system based on ultrasonic wave is designed with the position of the transmitter facing directly at the receiver, eliminating the reflection principle. Ultrasonic sensor works by measuring the traveling time of ultrasonic wave from the transmitter to the receiver. To measure the time unit, a counter system is used. In this research, the clock frequency used for the counter system is 97 kHz and 194 kHz as a variable. Both of the counter frequencies are used to map an object surface and the results will be compared. Based on the results, the counter frequency of 194 kHz generates more accurate contour than the frequency of 97 kHz.